The perils of race-thinking : a portrait of Aleš Hrdlička - Brandon, Mark A. (CEU Press studies in the history of medicine, 2023)
"Eugenics and scientific racism are experiencing a resurgence, and an understanding of the ideas of Aleš Hrdlička can help combat them. Today, the racial science of the early twentieth century is both untenable and contemptible. This book is about an arch figure of that period: Aleš Hrdlička served as Curator of Physical Anthropology at the prestigious Smithsonian Institution from 1910 to 1941. Although his ideas about race are today considered pseudoscience, the uncomfortable truth is that he was an internationally respected scientist in his own day.The Perils of Race-Thinking advances a bold new interpretation of modern racial ideology by exploring Hrdlička's intellectual world. Using previously untapped Czech-language sources, Brandon irrevocably alters the discussion about this important figure by placing Czech nationalism at the center of his racial thinking. Defying disciplinary categories, Perils of Race-Thinking joins critical analysis of this key American anthropologist with an incisive revisionist perspective of interwar Czechoslovakia to unearth transnational racial presumptions lurking behind the worst crimes of the twentieth century. At the center of Hrdlička's race beliefs was his commitment to Czech and Slovak unity and independence. From this center, his next level of concern was what he believed to be a millennial racial struggle between Germans and Slavs. On a global scale, he viewed the Slavs, and especially the Soviet Union, as a eugenic bastion of White strength holding off the "rising tide of color."Step by step, Perils of Race-Thinking mercilessly dismantles Hrdlička's racial system and exposes it as mysticism dressed up in the language of science. Convinced that human individuals belonged "naturally" in racial groups, Hrdlička embraced a revolutionary program of reordering the globe according to a harrowing morality of "Darwinist" struggle. Yet despite a lifetime of measuring body parts, even Hrdlička could not decide how many races there were or how to tell them apart"--